Management Strategies and Surgical Outcomes for Pediatric Appendicitis : A Literature Review - Wahyu Agus Prastyo; Artha Investari Nugraheni (International Medical Journal Corp. Ltd, 2025)
Background: The management of pediatric appendicitis has witnessed significant advancements, particularly with the introduction of non-operative strategies alongside traditional surgical approaches. Literature Review: The study by (GUANA et al., 2016) highlights the challenges of managing appendicitis in younger children, particularly under five years old, where atypical presentations can lead to complications such as perforation. The comparative analysis of laparoscopic and open surgical techniques underscores the benefits of minimally invasive surgery, including reduced postoperative pain and shorter recovery times, which are crucial in pediatric care. In contrast, the exploration of non-operative management by (Hall and Eaton, 2018) reveals that non-operative strategies, particularly antibiotic therapy, can be effective for uncomplicated appendicitis, with the potential to avoid surgery altogether. This perspective is supported by (Stulberg et al., 2018), who conducted a cost-effectiveness analysis demonstrating that antibiotic management yields better quality-adjusted life years and is less costly than surgical intervention. The systematic review by (Maita et al., 2019) further solidifies the efficacy of non-operative treatment for nonperforated appendicitis, indicating a significant success rate while acknowledging the need for careful patient selection to mitigate the risk of complications. The findings from (Yadao et al., 2022) and (Jumah and Wester, 2022) reinforce the potential of antibiotics as a first-line treatment for uncomplicated appendicitis, showcasing promising success rates and shorter hospital stays for non-surgical patients. Conclusion: In conclusion, the literature presents a compelling case for the evolving management strategies for pediatric appendicitis, advocating for a balanced approach that incorporates both surgical and non-operative options. As non-operative management gains traction, it is critical for clinicians to consider individual patient characteristics and the associated risks of recurrence and complications when determining the optimal treatment pathway.